2018
DOI: 10.1002/cam4.1770
|View full text |Cite
|
Sign up to set email alerts
|

USP14 as a novel prognostic marker promotes cisplatin resistance via Akt/ERK signaling pathways in gastric cancer

Abstract: Gastric cancer (GC) ranks the third leading cause of global cancer mortality. Despite recent progress in surgery combined with chemotherapy, the outcomes of GC patients have barely improved. Therefore, better understanding of the molecular mechanisms involved in chemoresistance of GC may help develop novel strategies to treat this deadly disease. Previous evidence has shown aberrant expressions of USP14 in multiple malignancies, suggesting an important role of USP14 in tumorigenesis. However, its role in modul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…Furthermore, the diversity of proteasomes can be increased by hundreds of proteasome-interacting proteins including the Ecm29 protein, the deubiquitinating enzymes Usp14, and Uch37, which have all either studied as or could become novel therapeutic targets (Figure 4) (267, 288, 295298). For example, Usp14 overexpression was observed in lung, breast, pancreatic, gastric, and endometrial cancer (289, 295, 299) and its inhibition via RNA interference or small molecule inhibitors resulted in reduced proliferation invasion and increased apoptosis in lung, breast, pancreatic, prostate, endometrial cancer, and melanoma cells (288, 289, 295, 296). The downregulation of Usp14 ensured smaller tumor sizes and longer survival in nude mice injected with lung cancer or melanoma cells (288, 289).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the diversity of proteasomes can be increased by hundreds of proteasome-interacting proteins including the Ecm29 protein, the deubiquitinating enzymes Usp14, and Uch37, which have all either studied as or could become novel therapeutic targets (Figure 4) (267, 288, 295298). For example, Usp14 overexpression was observed in lung, breast, pancreatic, gastric, and endometrial cancer (289, 295, 299) and its inhibition via RNA interference or small molecule inhibitors resulted in reduced proliferation invasion and increased apoptosis in lung, breast, pancreatic, prostate, endometrial cancer, and melanoma cells (288, 289, 295, 296). The downregulation of Usp14 ensured smaller tumor sizes and longer survival in nude mice injected with lung cancer or melanoma cells (288, 289).…”
Section: Discussionmentioning
confidence: 99%
“…USP10 and USP14 are independent predictors of prognosis for patients with GC, and the increased expression of USP10 in GC has been associated with the 5-year survival rate of patients. A previous study demonstrated that the downregulation of USP10, as well as the absence of USP14 expression in GC cells had significant effects on gastric wall invasion and lymph node metastasis, increased malignant biological behavior and reduced survival rate, as determined from a large number of clinical samples (44,45). Conversely, vimentin expression was upregulated in human GC tissues and cell lines as a result of deubiquitination, following interactions with USP14 and miR-320a, which may contribute to the aggressiveness of GC cells (46).…”
Section: Usps and Gcmentioning
confidence: 99%
“…Previous studies have reported that expression and activity of USP14 are elevated in gastric carcinoma, ovarian cancer and melanoma. Knockdown of this 19S proteasome-associated DUB sensitizes cancer to chemotherapeutics and induces apoptosis (25,26,50). To the best of ou knowledge, this evidence is the first to show that the expression and activity of USP14 are downregulated in A2780-CDDP cells and that the reduction in the expression and activity of USP14 is associated with cisplatin insensitivity.…”
Section: Discussionmentioning
confidence: 66%
“…USP14 disassembles the ubiquitin chain from its substrate-distal tip and serves as a quality control component to rescue proteins from degradation (22). Upregulation of USP14 is involved in the progression of non-small cell lung cancer (23), breast cancer (24), ovarian cancer (25) and gastric cancer (26). USP14 knockdown was found to suppress the proliferation and induced apoptosis of cancer cells.…”
Section: Inhibition Of Ubiquitin-specific Protease 14 Promotes Connexmentioning
confidence: 99%